KARAKTERISTIK DAN PENGETAHUAN AKSEPTOR KB SUNTIK DI DESA DONOMULYO LAMPUNG TIMUR - Redowati, Tusi Eka (Jurnal Kesehatan, 2022)
Contraception is an attempt to prevent pregnancy. This effort can be temporary or permanent. The use of contraceptives is one of the variables that affect fertility. The purpose of this study was to determine the characteristics and knowledge of injection family planning acceptors in Donomulyo Village. This study uses a descriptive method, the sample used is 199 and this research was carried out in Donomulyo Village. The results of the research on the characteristics and knowledge of injecting family planning acceptors in the village of Donomulyo, East Lampung, it is known that from 199 mothers of injecting family planning acceptors, most of them have a basic education level, namely 150 people (75.38%), secondary education as many as 43 people (21.61%) and higher education as many as 6 people (3.02%), based on work most of them do not work or only as housewives as many as 132 people (66.33%), based on economic status as many as 110 people (55.28%) low, multipara as many as 117 people (58.79%), most of them are in the age of 20-35 years as many as 142 people (71.36%), most of them have knowledge in the good category as many as 145 people (72.86 %). The conclusionis that most of the education level of injecting family planning acceptors is basic education, which is 150 people (75.38%). Most of the mothers who accept injections are not working, as many as 132 people (66.33%). The economic status of the mothers of injecting family planning acceptors mostly had low economic status, as many as 110 people (55.28%). The parity of injecting family planning acceptors were mostly multiparous, as many as 117 people (58.79%). the age of the mothers of injection family planning acceptors was mostly at the age of 20-35 years, as many as 142 people (71.36%).